Clubfoot: The Treatment Outcome Using Quantitative Assessment of Deformity. - Ahmad Hata, Rasit; H, Azani; PA, Zabidah; BA, Nur Alyana (Malaysian Orthopaedic Association, 2012)
The recent trend in management of congenital idiopathic clubfoot tends towards conservative treatment. This study reviews the outcomes of treatment in our practice using the quantitative clubfoot assessment of the deformity (QCAD). Methods: Thirty patients (38 cases of clubfoot) with congenital idiopathic clubfoot treated at Sarawak General Hospital were followed-up for a mean of 3.6 years. The quantitative assessment consists of limb anthropometric measurement and the Pirani deformity severity score.